IoT Enabled Intra-Vehicular Communication for Designing A Smart Car - Mohammad Hameez, Mat Zin; Ali, Jahan; Rahman, Md. Arafatur; Azad, Saiful; M. Nomani, Kabir (2016)
Nowadays, the number of sensor nodes in the vehicle has expanded altogether because of the expanding of various vehicular applications. Moreover, the wired connection is not adaptable and flexible due to the internal structure of the vehicle, thus, there is an expanding level of appeal to design a system in which the wired connections with the sensor node are supplanted with wireless connections. Design a wireless sensor system inside the vehicle is quite challenging than other systems, e.g., wireless, sensor and computer network, due to the unpredictable environment inside the vehicle. In this project, we discuss about Internet of Things (IoT) enabled Intra-Vehicular Communication for Designing a Smart Car. IoT enabled Intra-Vehicular Communication (IoT-IVC) refers to the system where huge number of sensors are associated with each other for sharing the car components’ information to build up a smart vehicular system. The marvel of congestion represents an issue in the IoT-IVC while the traffic load and number of sensors are expanded. A new scheduling algorithm is proposed for minimizing the congestion. A Test-Bed is designed in order to validate the proposed algorithm. The experimental results justify the effectiveness of the proposal.